A line search improvement of efficient MPC - Kouvaritakis, B; Li, S; Cannon, M (Elsevier, 2010)
A recent efficient Model Predictive Control (MPC) strategy uses a univariate Newton-Raphson procedure to solve a dual problem, but is not amenable to warm starting or early termination. By solving a primal problem, the current note proposes a strategy which is more efficient than the Newton-Raphson method and which enables warm starting and early termination. Performance improvements are demonstrated over the Newton-Raphson method and alternative approaches based on quadratic programming or semidefinite programming.